2015
DOI: 10.1016/j.actamat.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of energy and atomic solubility of twinning-associated boundaries in hexagonal metals

Abstract: Twinning-associated boundaries (TB), f1 0 1 ng coherent twin boundaries (CTB) and the coherent basal-prismatic (CBP) boundary in six hexagonal metals (Cd, Zn, Mg, Zr, Ti and Be) are studied using first-principles density function theory, with the focus on the structural character of TB and the solute's solubility at TB. Regarding the structure and energy of TB, the formation of TB is associated with the creation of an excess volume. All six metals show positive excess volume associated with ð1 0 1 1Þ and ð1 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 55 publications
3
47
1
Order By: Relevance
“…The most pronounced transition from covalent to metallic bonding takes place in basal SF, which results in large g SF (pure Ti) values of this system. Recent investigations revealed that a-Ti solutes have better solubility in twin boundaries (TB) than in bulk, due to the excess volume of the twin-bulk structure interface [19]. Since both TB and SF exhibit many common features, a-Ti SFs interplanar distance distortion r (difference of interplanar distance between distorted and unstrained crystal) is plotted in Fig.…”
Section: Electronic and Atomic Structures Of A-ti Stacking Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most pronounced transition from covalent to metallic bonding takes place in basal SF, which results in large g SF (pure Ti) values of this system. Recent investigations revealed that a-Ti solutes have better solubility in twin boundaries (TB) than in bulk, due to the excess volume of the twin-bulk structure interface [19]. Since both TB and SF exhibit many common features, a-Ti SFs interplanar distance distortion r (difference of interplanar distance between distorted and unstrained crystal) is plotted in Fig.…”
Section: Electronic and Atomic Structures Of A-ti Stacking Faultsmentioning
confidence: 99%
“…[17,18] with the conclusion that O stabilizes/destabilizes basal/prismatic faults, respectively. The next important feature of the planar defects e twin boundaries (TB) reported lately [19], show better solubility of many Ti alloying atoms in TB than in bulk. This unique phenomenon was correlated with the excess TB volume delocalized within 4e5 atomic planes, implying relatively large TB e solute interaction distance.…”
Section: Introductionmentioning
confidence: 99%
“…It differs from vertical atomic-layer-resolved shifts that are analyzed, for example, in the recent study by Kumar et al [72]. The individual inter-layer distances significantly differ from the bulk equilibrium value (0.799 Å) with the extreme values of these deviations being (i) +0.33 Å for the distance between the GB plane and the first atomic layer off the GB plane and (ii) –0.26 Å between the first and second plane off the GB plane, respectively, in the Σ5(210) Al,Ni .…”
Section: Resultsmentioning
confidence: 86%
“…Specifi cally, DFT calculations show that solute solubility has little dependence on the radius of solute atoms along CTB, but varies considerably with stresses on PBs. 69 …”
Section: Deformation Twinning In Hexagonal Materialsmentioning
confidence: 99%